Stent-Coil Treatment of a Distal Internal Carotid Artery Dissecting Pseudoaneurysm on a Redundant Loop by Use of a Flexible, Dedicated Nitinol Intracranial Stent - Pride, G. Lee; Replogle, Robert E.; Rappard, George; Graybeal, Christopher L. Taylor Dion; White, Jonathan; Purdy, Phillip (American Journal of Neuroradiology, 2004)
Summary: Treatment of dissecting pseudoaneurysms of the distal cervical internal carotid artery with preservation of the parent artery by using stents or coils has become routine. Tortuosity remains a significant obstacle to successful endovascular treatment in some cases. We report the use of a stent-coil technique to treat a nonhealing dissecting pseudoaneurysm and associated stenosis with anatomic preservation of a redundant loop involving the stented arterial segment. This was accomplished by using a Neuroform dedicated intracranial stent.